1981
DOI: 10.1103/physrevc.24.1363
|View full text |Cite
|
Sign up to set email alerts
|

O16(γ,p)

Abstract: The O(y, po) reaction has been studied with linearly polarized bremsstrahlung photons in and below the giant E1 resonance. The parity of the absorbed radiation was determined from the observed azimuthal asymmetry of the emitted protons. Combined with unpolarized measurements the polarized results determine the proton decay amplitudes of the M1 resonance at E"=16. 2 MeV in O. The shape of the unpolarized O(y, p3) angular distribution in the giant E1 resonance was derived from the measured analyzing power. NUCLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The 16.2-MeV I + state in 160 could also be observed in an experiment with polarized bremsstrahlung (49), and it was shown that the Ci>, particle) reaction provides new information about decay amplitudes of overlapping unbound states of different parity and/or different multipolarity, infor mation not obtainable from unpolarized measurements. The measured 1 60 (y, p) spectrum is depicted in Figure 15 results of the inelastic electron scattering experiment (75) (1.12 ± 0.07 f1�), but in addition to the ground-state decay width, the partial decay widths to other states could be measured in NRF (77).…”
Section: 1mentioning
confidence: 95%
See 2 more Smart Citations
“…The 16.2-MeV I + state in 160 could also be observed in an experiment with polarized bremsstrahlung (49), and it was shown that the Ci>, particle) reaction provides new information about decay amplitudes of overlapping unbound states of different parity and/or different multipolarity, infor mation not obtainable from unpolarized measurements. The measured 1 60 (y, p) spectrum is depicted in Figure 15 results of the inelastic electron scattering experiment (75) (1.12 ± 0.07 f1�), but in addition to the ground-state decay width, the partial decay widths to other states could be measured in NRF (77).…”
Section: 1mentioning
confidence: 95%
“…A breakthrough for NRF experiments with bremsstrahlung was the development of the linearly polarized bremsstrahlung beam facility at the University of Giessen 65-MeV electron linear accelerator (11,49). With this experimental arrangement it was possible for the fi rst time to determine parities of highly excited dipole states close to the particle threshold in an NRF measurement and to study systematically the spin-flip M I resonance, which is located around 10 MeV.…”
Section: Linearly Polarized Photonsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was extrapolated below the 6-MeV detection threshold of the polarimeter by dashed lines using the known energy dependence of the photon polarization. 15 The width of these lines gives the statistical accuracy of the 2 H(y pol ,/>) measurement. The error bars (one standard deviation) show the measured asymmetries for the strongest transitions.…”
mentioning
confidence: 99%
“…Polarized photon beams [ 1,2] have been interested in the field of the nuclear physics, because the real photon has a high spin selectivity and ambiguous parity assignment has been done [3]. Almost completely linearly polarized photon beam was generated by Compton backscattering of linearly polarized laser photons in several facilities [4][5][6], because of the small spin-flip amplitude in the Compton scattering at the forward direction.…”
mentioning
confidence: 99%